Dimitri Van Limbergen, The Resilience of the Roman Empire: Regional case studies on the relationship between population and food resources (BAR International Series 3000). - McLean , Andrew (Journal of Greek Archaeology, 2024)
Studies attempting to better understand the ancient economy have become increasingly popular amongst archaeological researchers in recent years. It is a broad, complex and often daunting topic to engage with, but one which can produce extremely insightful results with wide reaching implications for studies of past societies and archaeology more broadly. The Roman Empire represents a particularly fertile ground for understanding ancient economies, with a relatively long and stable history covering a large expanse of diverse landscapes, with complex economic networks connecting the disparate corners of the Empire.